2014
DOI: 10.1186/1471-2318-14-24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a home visiting nurse intervention versus care as usual on individual activities of daily living: a secondary analysis of a randomized controlled trial

Abstract: BackgroundHome visiting nurses (HVNs) have long been part of home and community-based care interventions designed to meet the needs of functionally declining older adults. However, only one of the studies including HVNs that have demonstrated successful impacts on Activities of Daily Living (ADL) has reported how those interventions affected individual ADLs such as bathing, instead reporting the effect on means of various ADL indices and scales. Reporting impacts on means is insufficient since the same mean ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…The results of these studies may be biased due to a small sample size. On the other hand, the results were consistent with the results of studies that used a large sample size (Friedman et al, 2009, Friedman et al, 2014and Meng et al, 2009. It is important to highlight that the self-management support programmes in a lot of studies were provided in addition to usual care.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The results of these studies may be biased due to a small sample size. On the other hand, the results were consistent with the results of studies that used a large sample size (Friedman et al, 2009, Friedman et al, 2014and Meng et al, 2009. It is important to highlight that the self-management support programmes in a lot of studies were provided in addition to usual care.…”
Section: Discussionsupporting
confidence: 81%
“…This may therefore result in an overestimation of the effect of self-management support programmes. However, studies were included in the present review that reported no significant effect of self-management support programmes on the activities of daily living of older adults (Elzen et al, 2007, Friedman et al, 2014, Meng et al, 2009, Sundsli et al, 2014and Wetzels et al, 2008. In some studies a small sample size was used (Alp et al, 2007, Ersek et al, 2003, Girdler et al, 2010and Sundsli et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A nursing diagnosis determines nursing care interventions. Many of interventions implemented towards universal self‐care requisites needs' aim to improve or to prevent further impairment (Friedman et al 2014). In our findings, the nursing diagnoses point out to the individual’s resources and its potentiality to overcome the impairment.…”
Section: Discussionmentioning
confidence: 99%